Sketches and CAD, partners in architectural design: experience at the Catholic University of the North (Chile) - Vergara-Valverde, Francisca del Pilar; Pérez-Lancellotti, Gino (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
The prominence of sketching and architectural observation has been displaced by the increasing use of CAD tools among architecture students. However, the thesis that these tools can be effectively used together is defended. The research employs a mixed-method design with two sequential phases. Firstly, the prevalence of CAD representations and the use of sketches in two-thirds of the projects are recognized for a sample of 102 thesis projects from the School of Architecture of Catholic University of the North-Chile. In the second phase, through a case study, the symbiosis of sketches with CAD, particularly in their prescriptive and speculative functions, is demonstrated. The article contributes to the discussion on the integration of analog and digital approaches in architectural education and prompts reflection on the continued relevance of sketches as an identity hallmark in the aforementioned school.